Prevalence of Dyslipidemia in Urban and Rural Areas of the Northwest of Iran: The Sociodemographic, Dietary and Psychological Determinants - Jafar Sadegh TABRIZI; Leila NIKNIAZ; Homayoun SADEGHI-BAZARGANI; Mostafa FARAHBAKHSH; Zeinab NIKNIAZ; Mahdieh ABBASALIZAD FARHANGI; Elham EGHBALI (Tehran University of Medical Sciences, 2019)
Background: As dyslipidemia is a preventable risk factor for Coronary heart disease (CHD), precise estimation of its prevalence and determinants is crucial for proper development of health actions. This population-based study aimed at investigating the socioeconomic, dietary and psychological determinants of dyslipidemia in Iran. Methods: The data (n=700) for this study were collected in 2015 as a part of the major Lifestyle Promotion Project (LPP) conducted in East Azerbaijan (urban and regional parts). The data for socio-demographic status, dietary information, and physical activity and anxiety levels were collected through validated questionnaires. Then, physical examinations including blood pressure, body mass index (BMI) and conicity index were performed. The levels of serum lipids were measured by enzymatic colorimetric methods. Results: The prevalence of hypercholesterolemia, high LDL-C, hypertriglyceridemia, low HDL-C and dyslipidemia was 29.4%, 10.3%, 62.3%, 41.4%, 83.3% respectively. The mean TC (184.3±41.2 vs. 174.5±38.1 mg/dl), LDL-C (94.6±30.3 vs. 88.1±28.7 mg/dl) and HDL-C (46.7±10.4 vs. 39.5±8.0 mg/dl) in women were significantly higher than men (P<0.05). However, the mean of TG (182.3±119.3 vs. 145.1±87.8 mg/dl) was significantly higher in men compared to women (P<0.05). Obesity, family history of dyslipidemia, sedentary lifestyle, smoking habits, salt intake, and anxiety were risk factors for different components of dyslipidemia in men and women. Conclusion: Dyslipidemia is a major health problem in northwest of Iran. Focusing on screening, regular drug intake, proper nutrition, physical activity, and changing lifestyles of patients with dyslipidemia are essential.